The relationship between supply chain management and competitiveness - Pinzón Castro, Sandra Yesenia; Maldonado Guzmán, Gonzalo; López Torres, Gabriela Citlalli (Mercados y Negocios, 2016)
The globalization of the markets and the new business environmental are forcing organizations, mainly the small and medium-sized enterprises, to improve their competitiveness significantly since to remain in the current market it is necessary to modify the managerial strategies to adapt them to the changes and the clients’ requirements. In this sense, supply chain management appears in the literature like one of the managerial strategies that are implementing in important number of firms to be able increase competitiveness. Therefore, the essential objective of this paper is to analyze the relationship between supply chain management and the competitiveness of small and mediumsized enterprises, using for it a sample of 305 firms of the Aguascalientes State. The obtained results show that supply chain management has a positive influence in competitiveness level, as well as in the financial performance, cost reduction and the use of technology of the small and medium-sized enterprises.